Functional dimensions at 'Kuala Lumpur Waterfront' - Abdul Latip, Nurul Syala; Shamsudin, Shuhana; Liew, Mohd Shahir (Universiti Teknologi Mara Malaysia, 2010)
Kuala Lumpur waterfront used to be busy with activities when it was once a trading post for the export of tin. The activity at the waterfront has changed over the years along with the city development. This research investigates the level of contextual integration between the waterfront and the urban rivers in terms of its functional dimension. Technique adopted is field observations (building use survey and time interval observation). All researched zones have medium level of contextual integration which depends much on the continuity of activities, their positioning location, accessibility and the provision of space and facilities.